Combining spatial and temporal expectations to improve visual perception. - Rohenkohl, G; Gould, I; Pessoa, J; Nobre, A (2014)
The importance of temporal expectations in modulating perceptual functions is increasingly recognized. However, the means through which temporal expectations can bias perceptual information processing remains ill understood. Recent theories propose that modulatory effects of temporal expectations rely on the co-existence of other biases based on receptive-field properties, such as spatial location. We tested whether perceptual benefits of temporal expectations in a perceptually demanding psychophysical task depended on the presence of spatial expectations. Foveally presented symbolic arrow cues indicated simultaneously where (location) and when (time) target events were more likely to occur. The direction of the arrow indicated target location (80% validity), while its color (pink or blue) indicated the interval (80% validity) for target appearance. Our results confirmed a strong synergistic interaction between temporal and spatial expectations in enhancing visual discrimination. Temporal expectation significantly boosted the effectiveness of spatial expectation in sharpening perception. However, benefits for temporal expectation disappeared when targets occurred at unattended locations. Our findings suggest that anticipated receptive-field properties of targets provide a natural template upon which temporal expectations can operate in order to help prioritize goal-relevant events from early perceptual stages.